1994
DOI: 10.21273/hortsci.29.8.850
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thinning of Peaches is Effective Postbloom

Abstract: Hand-thinning (Prunus persica L. Batsch) “Y”-trained peach trees at bloom and 51 days after full bloom (DAFB) was compared to mechanical fruit thinning 51 DAFB using a spiked-drum and an impact shaker. The spiked-drum shaker removed more fruit from horizontal branches than from vertical branches, yet did not selectively remove either large or small fruit. Bloom thinning by hand increased fruit size compared to postbloom thinning 51 DAFB, and both postbloom mechanical thinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 5 publications
1
18
0
1
Order By: Relevance
“…The preliminary tests carried out in this study confirmed that the new thinner developed in France can be used on stone fruit both at blooming and at the green fruit stage, with minimal harm to the branches or the fruits even when thinning is performed at a more advanced fruit growth stage. Either in apricot and peach, the machine did not seem to selectively remove either large or small fruit, similar to what was found in other studies of mechanical fruit thinning [2,38,39]. However, as found in other tests with the same machine (7), the results varied largely, being affected by the species, the cultivar, the flowers and/or fruit loads, and the shoot length.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The preliminary tests carried out in this study confirmed that the new thinner developed in France can be used on stone fruit both at blooming and at the green fruit stage, with minimal harm to the branches or the fruits even when thinning is performed at a more advanced fruit growth stage. Either in apricot and peach, the machine did not seem to selectively remove either large or small fruit, similar to what was found in other studies of mechanical fruit thinning [2,38,39]. However, as found in other tests with the same machine (7), the results varied largely, being affected by the species, the cultivar, the flowers and/or fruit loads, and the shoot length.…”
Section: Discussionsupporting
confidence: 81%
“…Tests were carried out on narrow-canopied orchards, more easily accessible, and hence best suited to the penetration of thinning elements such as strings or rods [2,11,22] during blooming time and on Sustainability 2018, 10, 4088 4 of 12 green fruit. The trials were carried out in March-May 2016 on two apricot and two peach commercial orchards, located in the provinces of Forlì-Cesena and Ravenna, northeast Italy.…”
Section: Orchard Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Link 2002). Neben der chemischen und Handausdünnung kommt seit einigen Jahren eine interessante Alternative hinzu: die mechanische Blütenausdünnung mittels einer Ausdünnma-schine (Menzies 1980;Smith u. Galliott 1990;Glenn et al 1994;Stimmer u. Kelderer 1997;Handschack 1999;Weibel u. Walther 2003).…”
unclassified